Numerical study on blasting damage of rock with eccentric charge structure - Kaihua Liang; Hong Zhao; Yang Li; Weihui Pan; Fuwu Ma; Hai Rong; Nannan Li (PLoS ONE, 2026)
To enhance the safety and efficiency of blasting operations in mines, this study numerically investigates the influence of eccentric versus concentric decoupled charge structures on rock fragmentation under constant charge mass. Using ANSYS/LS-DYNA simulations, the distribution of effective stress (ES) and crack propagation patterns around a single borehole were analyzed. Damage evolution was quantitatively assessed through the damage area ratio (DAR) metric. The results indicate that eccentric charges induce an asymmetric stress field, with ES on the coupled side being up to 2.29 times higher than that on the uncoupled side, and promote vertically symmetrical crack propagation with higher crack density near the charge. The influence range of eccentric charging is limited. Beyond this range, the stress field converges to that produced by concentric charging. Compared to a single charge, multi-charge layouts (double/triple) significantly improve blasting effectiveness, with the optimal structure depending on the number of charges: bottom-eccentric for single or double charges, and concentric for triple charges. These findings provide concrete theoretical guidance for designing controlled blasting schemes in engineering applications such as soft rock blasting, presplitting, and roadway excavation in hard rock formations.